Al–RE Intermetallic Phase Stability and Effects on Corrosion Behavior in Cold‐Chamber HPDC AE44 Alloy1. Issue 1 (14th July 2015) - Jiao, Yufeng; Zhang, Jinghuai; He, Lili; Zhang, Milin; Jiang, Fengchun; Wang, Wei; Han, Liming; Xu, Longjiang; Wu, Ruizhi
Abstract : Mg–4Al–4RE (wt%, AE44) alloy is prepared by cold‐chamber high‐pressure die‐casting (HPDC). The microstructure, thermal stability of Al–RE phases and its effect on corrosion behavior are investigated. The main strengthening phase is Al11RE3, which is thermally instable when heated at 400 °C. Some Al11RE3 would be transformed to Al2RE. The alloy in HPDC state exhibits relatively high corrosion resistance due to the Al11RE3 at grain boundaries that can act as the corrosion barrier. While after heat treatment at 400 °C for 1000 h and 5000 h, the corrosion resistance performance degrades due to the changes of morphology and distribution of Al–RE phases. Abstract : Mg–4Al–4RE (wt%, AE44) alloy is prepared by cold‐chamber high‐pressure die casting (HPDC). The Al–RE phases are investigated by qualitative and quantitative analyses. The microstructure of Al11 RE3 would be changed when heated at 400 °C. While after heat treatment at 400 °C for 1000 h and 5000 h, the corrosion resistance performance degrades due to the changes of morphology and distribution of Al–RE phases.